P-109 Randomised clinical trials in a hospice setting: toil, tribulations, triumph. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Hall, Charlie; Cook, Jane; Blackwood, Honor; Haraldsdottir, Erna; Brown, Duncan; Maddocks, Matthew; Dixon, Liz; Skipworth, Richard; Fallon, Marie; Laird, Barry
Abstract : Background: Despite clinical research being advocated as a key component of palliative care (Payne, Preston, Turner & Rolls, 2013), most patients under the care of palliative care services will not have the opportunity to participate in research. Of the 200 plus UK hospices, few patients get the opportunity to actively participate in research for multiple reasons including lack of expertise, funding, opportunity and anxiety about excess patient burden. However even patients with advanced disease describe multiple benefits from being involved in research trials (Middlemiss, Lloyd-Williams, Laird & Fallon, 2015) and it is possible to establish and conduct clinical trials within the hospice setting. Aim: To describe the experience of establishing and conducting a randomised clinical trial in an independent UK hospice. Results: The ethical, logistical and regulatory hurdles to establishing a clinical trial are described and include local engagement, funding, sponsorship, developing academic links and tackling barriers to recruitment. Novel initiatives are described, including volunteer and carer engagement and motivating team members to realise the advantages of in-house clinical trials. Further, the image of hospice care was improved through the establishment of a research culture. Conclusions: It is possible to establish and conduct clinical trials within a UK hospice setting; and this has multiple advantages to patients and staff alike.